Action Research : Bridging the Gap between Teaching and Researching - Alemán, María José (2009)
This paper aims to discuss ways in which teachers’ professional practice can be improved by implementing action research projects. It seeks to explain in simple terms the key aspects involved in carrying out classroom research and how investigation and teaching can be linked. Action research can help teachers find solutions to some of the problems they find in their classes by encouraging them to adopt a reflective, systematic and critical approach to deal with those issues. As action research is basically collaborative in nature, it helps teachers exchange views and experiences, discuss problems and work out possible solutions together as a team. Action research is presented as a means to improve teachers’ professional practice based on informed decisions rather than on intuition. El objetivo de este trabajo es analizar en qué forma la práctica docente puede ser mejorada implementando proyectos de investigación-acción. Procura explicar en términos simples los aspectos fundamentales que deben ser tenidos en cuenta para desarrollar investigación áulica. Asimismo intenta establecer cómo se puede vincular la investigación y la enseñanza. La investigación-acción puede ayudar a los profesores a encontrar soluciones a los problemas que enfrentan en el aula, alentándolos a adoptar un enfoque reflexivo, sistemático y crítico para resolver estas cuestiones. Al ser básicamente colaborativa por naturaleza, la investigación-acción alienta a los profesores a intercambiar puntos de vistas y experiencias, analizando los problemas y trabajando en equipo para encontrar soluciones. La investigación-acción es vista como una forma de mejorar la práctica profesional docente basada en el conocimiento del problema y no en la intuición.